1994
DOI: 10.1210/endo.135.3.8070384
|View full text |Cite
|
Sign up to set email alerts
|

Maternal insulin-like growth factor-I infusion alters feto-placental carbohydrate and protein metabolism in pregnant sheep.

Abstract: Insulin-like growth factor-I (IGF-I) in the maternal circulation may have a role in the regulation of placental function and fetal growth, but its mechanisms of action are not known. We studied the effects of maternal IGF-I infusion (30 micrograms/kg.h for 4 h) in eight chronically catheterized pregnant sheep. IGF-I infusion caused an increase in fetal blood glucose concentrations, but no change in placental or fetal glucose uptake. Maternal plasma insulin concentrations fell. Placental lactate production incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…This is supported by the findings that the UmBF in the EL group was higher than in EH and control groups, and this increased blood flow was sufficient to maintain foetal glucose uptake in EL foetuses, associated with normalisation of foetal growth rate after embolisation ceased. Maternal IGF-1 concentrations were also increased in the EL group, and this may also have contributed to a compensatory increase in utero-placental glucose uptake and hence foetal growth [32] . Furthermore, concentrations of many maternal amino acids were elevated in the EL group compared to both EH and control groups, a phenomenon commonly seen in human IUGR pregnancies [33] .…”
Section: Discussionmentioning
confidence: 92%
“…This is supported by the findings that the UmBF in the EL group was higher than in EH and control groups, and this increased blood flow was sufficient to maintain foetal glucose uptake in EL foetuses, associated with normalisation of foetal growth rate after embolisation ceased. Maternal IGF-1 concentrations were also increased in the EL group, and this may also have contributed to a compensatory increase in utero-placental glucose uptake and hence foetal growth [32] . Furthermore, concentrations of many maternal amino acids were elevated in the EL group compared to both EH and control groups, a phenomenon commonly seen in human IUGR pregnancies [33] .…”
Section: Discussionmentioning
confidence: 92%
“…We have previously shown that short-term infusion of IGF-I into the maternal or fetal circulations alters placental metabolism, especially of lactate, suggesting that placental function can be influenced by maternal and fetal endocrine status (16,17). In those studies, maternal IGF-I infusions sufficient to increase maternal plasma IGF-I levels 3-fold for 3 h approximately doubled placental lactate production and fetal lactate uptake.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously shown in pregnant sheep that shortterm infusion of IGF-I to the mother results in metabolic changes consistent with an increase in substrate uptake from mother to fetus (16), whereas IGF-I infusion to the fetus results in fetal anabolic changes (17). We have therefore speculated that prolonged elevation of IGF-I concentrations on both sides of the placenta would be expected to lead to enhanced fetal growth (16).…”
Section: F Etal Growth In Late Gestation Is Limited Largely Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin promotes lipogenesis within the maternal compartment, mediating glucose and amino acid uptake by the adipose and muscle tissue (Vernon et al, 1981;McNeill et al, 1997). IGF-I, in contrast, influences the placental transfer of glucose and amino acids (Kniss et al, 1994;Liu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%